Description of immatures of Stolas aenea (Olivier, 1790) and Stolas nudicollis (Boheman, 1850) (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini) - Leocádio, Michele; Mermudes, José Ricardo M. (Zootaxa, 2019)
Immature stages of Stolas aenea and S. nudicollis are described based on specimens collected in Rio de Janeiro, Brazil. Descriptions including chaetotaxy, illustrations and photographs (including SEM images) are given for eggs, first and last instar stages. New host plant records are presented for both species. This is the first detailed description for any species in the genus Stolas. Morphological comparisons with other Mesomphaliini species are provided.